O papel das macrófitas aquáticas nos processos erosivos, qualidade da água e dinâmica de gases do efeito estufa no Pantanal norte - Bühler, Beatriz Ferraz (2020)
In wetlands such as the Pantanal, aquatic macrophytes tend to stabilize and perform relevant ecological functions through water level fluctuations that determine the structure and dynamics of the environment. This study sought to evaluate the role of aquatic macrophytes in erosive processes, water quality and greenhouse gas dynamics in six bays on the Paraguay River, North Pantanal. For this purpose, field campaigns were carried out between January/2017 to July/2018, considering the flood and dry periods of the Pantanal, to monitor marginal erosion, collect material (water, sediment and plant) and survey variables (hydrodynamics and greenhouse gases). The material collected in the field was analyzed in a laboratory where an anaerobic decomposition experiment was also carried out with the species Eichhornia azurea and Eichhornia crassipes. The treatments that outlined this study were considered as follows: 1 - center of the bays; 2 - shore with macrophytes; 3 - shore without macrophytes. In this way, the magnitude of erosion, the water quality index (WQI), the degree of hemeroby, the concentration and diffusion flows of carbon dioxide (CO2) and methane (CH4) in the water and the data were discussed from the perspective of the presence and absence of macrophyte beds. An anaerobic decomposition experiment was performed out during 60 days at two temperatures (29 °C and 31 °C). The results showed that the aquatic vegetation beds in marginal bays function as containment structures against waves caused by boats in fishing environments (p < 0.05). Regarding water quality, aquatic macrophytes have been shown to improve the WQI in bays close to the urban area and the WQI showed significant differences between periods of flood and drought (p <0.001). The degrees of hemeroby demonstrated that the bays are mostly classified between the grades ahemerobic, oligohemerobic and mesohemerobic. When related to the WQI and the degree of hemeroby, the results showed that in areas whose capacity for self-regulation is higher, water hyacinth beds tend to increase the WQI (R² = 0.19; p <0.05) while in areas with low capacity for self-regulation, WQI tends to be reduced by the presence of macrophytes (R² = 0.27; p < 0.05). Regarding the anaerobic decomposition processes, the E. crassipes presents a decay due to loss of mass 1.6 times greater at 31 °C than at 29 °C, but the species E. azurea does not present differences. The diffusive flow of methane showed that the diffusion of methane in the water is greater than 50 cm in depth without the macrophyte bed (p < 0.05) and the concentration of methane in the water was significantly higher in the aquatic macrophyte beds (p = 0.01). Therefore, it was possible to conclude that aquatic macrophytes play an important role in containing marginal erosion, in limnological conditions and in the dynamics of formation, assimilation and release of greenhouse gases in Pantanal bays.